Pandangan Hukum Islam Terhadap Pernikahan Dini - Dinar Rosyiddin Alifian Romadhon (CV Edujavare Publishing, 2024)
The purpose of writing this work is to find out the view of Islamic law towards early marriage. This research adopts a qualitative methodology with a library research approach, using literary data collection techniques from primary and secondary sources. The data analysis technique applied is content analysis, with a focus on detailed exploration of the content and authorship dimensions of the books studied. Overall, this research explores a deep understanding of the research object through systematic collection and analysis of literary data. The result of this work is that the Islamic view of marriage emphasizes its dimensions as a combination of sacredness, worship and moral foundations. In this context, marriage is not just a marriage contract, but also a complex and flexible religious obligation. In conclusion, marriage in Islam is a deep worship, becoming the basis for happiness and blessings in this world and the hereafter. Early marriage, involving couples under the age of 18, creates complex and controversial problems in society. Despite support from some Islamic law scholars, there is controversy regarding its validity, especially regarding the marriage of the Prophet Muhammad SAW to Aisyah at the age of six. A review of Islamic law and legislation confirms the need for a holistic approach to protecting the rights and well-being of young individuals in the context of early marriage.